The Construction of Body Image Scale in Early Adult Women - Kuncoro, Prayogo Agus; Salsabila, Savara; Puspitasari, Elysa Diana; Rahmawati, Annisa; Cahyani, Dewi Agus; Kurniawan, Fredirikus Bayu; Husna, Aftina Nurul (Prosiding University Research Colloquium, 2021)
The purpose of this research is to develop the right instrument to measure body image.Body image is a picture held in the mind of an individual about the size, shape, andindividual feelings about the characteristics and body parts that make up the individual.In McCabe's theory, there are five dimensions/aspects of body image: Body ImageImportance, Body Concealment, Body Improvement, Social Physicue Anxiety, AppearanceComparison. The participants involved in the scale trial that the researchers conductedwere 60 participants. Data was collected through an online survey. The samplingtechnique used was non-random sampling with Snowball-Sampling. Psychometric testresults show that, the value of Cronbach's Alpha which shows the number 0.909 out of 20items, which means this measuring instrument has good reliability. Correlation Item-TotalStatistics shows the correlation between one item and another item is more than 0.30.